Polarimetric properties of the near-Sun asteroid (155140) 2005 UD in comparison with other asteroids and meteoritic samples. Issue 3 (9th November 2021) - Ishiguro, Masateru; Bach, Yoonsoo P; Geem, Jooyeon; Naito, Hiroyuki; Kuroda, Daisuke; Im, Myungshin; Lee, Myung Gyoon; Seo, Jinguk; Jin, Sunho; Kwon, Yuna G; Oono, Tatsuharu; Takagi, Seiko; et al.
ABSTRACT: The investigation of asteroids near the Sun is important for understanding the final evolutionary stage of primitive Solar system objects. A near-Sun asteroid (NSA), (155140) 2005 UD, has orbital elements similar to those of (3200) Phaethon (the target asteroid for the JAXA's DESTINY + mission). We conducted photometric and polarimetric observations of 2005 UD and found that this asteroid exhibits a polarization phase curve similar to that of Phaethon over a wide range of observed solar phase angles (α = 20–105°) but different from those of (101955) Bennu and (162173) Ryugu (asteroids composed of hydrated carbonaceous materials). At a low phase angle (α ≲ 30°), the polarimetric properties of these NSAs (2005 UD and Phaethon) are consistent with anhydrous carbonaceous chondrites, while the properties of Bennu are consistent with hydrous carbonaceous chondrites. We derived the geometric albedo, p V ∼ 0.1 (in the range of 0.088–0.109); mean V -band absolute magnitude, H V = 17.54 ± 0.02; synodic rotational period, $T_rot = 5.2388 ± 0.0022 \, h$ (the two-peaked solution is assumed); and effective mean diameter, $D_eff = 1.32 ± 0.06 \, km$ . At large phase angles (α ≳ 80°), the polarization phase curve are likely explained by the dominance of large grains and the paucity of small micron-sized grains. We conclude that the polarimetric similarity of these NSAs can be attributed to the intense solar heating of carbonaceous materials around their perihelia, where large anhydrous particles with small porosity could be produced by sintering.